Mechanisms in the analysis of macro-social phenomena - Renate Mayntz (Max Planck Institute for the Study of Societies, 2003)
The paper is a contribution to a forthcoming special issue of the Journal Philosophy of the Social Sciences, edited by Andreas Pickel. The term (social) mechanism can be found frequently in recent social science literature, but only few authors have attempted to spell out systematically what exactly the term refers to. The paper begins by trying to close this gap. Use of the term (social) mechanism is the hallmark of an approach that is critical of the emphasis on correlational analysis, and on the covering-law model of explanation. The term mechanism, it is argued, should be used to refer to recurrent processes generating a specific kind of outcome or event; mechanism statements are accordingly statements about recurrent processes. Explanation of social macro phenomena by mechanisms typically involves causal regression to lower level elements, as stipulated by methodological individualism. But while we already have a good-sized tool-box of mechanism models at hand to explain emergent effects of different forms of collective behavior, we lack a similarly systematic treatment of generative mechanisms where structural configurations and corporate actor constellations play the decisive role in the production of an effect. – – Das Papier wird als Aufsatz in einem von Andreas Pickel herausgegebenen, in Vorbereitung befindlichen Sonderheft der Zeitschrift Philosophy of the Social Sciences erscheinen. Der Begriff (sozialer) Mechanismus findet sich relativ häufig in der neueren sozialwissenschaftlichen Literatur, aber nur wenige Autoren widmen sich einer systematischen Begriffsklärung, wie sie hier einleitend versucht wird. Mit der Verwendung des Begriffs (sozialer) Mechanismus ist gewöhnlich eine Kritik am korrelationsanalytischen Ansatz und an nomologisch-deduktiver Erklärung verbunden, die den Prozesscharakter sozialer Wirklichkeit ausblenden. Der Begriff Mechanismus, so wird argumentiert, sollte speziell zur Bezeichnung wiederkehrender Prozesse dienen, die am Zustandekommen bestimmter Makrophänomene beteiligt sind. Eine Erklärung von Makrophänomenen durch Mechanismen geschieht gewöhnlich durch kausale Regression auf eine niedrigere Systemebene. Das entspricht dem Modell des methodologischen Individualismus, der allerdings durch die Reduktion auf individuelles Handeln jenen Transformationsmechanismen kaum gerecht wird, bei denen strukturelle Konfigurationen und Akteurkonstellationen die kausal entscheidende Rolle spielen.
Keywords: 300